Prevalence and Occlusal Risk Factors for Fractured Incisors among 11-12-Year-Old Children in the Trinidad and Tobago Population - Trudee Hoyte; Anne Kowlessar; Anil Ali; David Bearn (MDPI AG, 2020)
This cross-sectional survey was carried out to ascertain the prevalence of fractured incisors in 11−12-year-olds. In addition we explored the relationship with overjet, incompetent lips, incisor inclination and to determine if there was any association with ethnicity and gender. All permanent incisors were examined in 672 children comprising 356 females (53.1%) and 315 males (46.9%). The sample comprised 11−12-year-olds in high schools across Trinidad and Tobago. Statistical analysis was undertaken using Chi-square test, independent t-test, and binary logistic regression. The prevalence of fractured incisors was 18.9%. Boys presented with an increased incidence of fractured incisors than girls. 86.3% of dental trauma was untreated. The average overjet of subjects with fractured incisors was 4.2 mm. 18.62% of subjects with fractured incisors had incompetent lips. The most common malocclusion (18.81%) with fractured incisors was class 2 division 1. The Afro-Trinidadian ethnicity had the highest prevalence of fractured incisors (11.0%) when compared to mixed ethnicities, which was statistically significant. Maxillary central incisors were the most commonly injured teeth. Most patients delayed in seeking dental treatment for fractured incisors in our population. Early orthodontic treatment is recommended to help reduce the risk of dental trauma.